2021
DOI: 10.6001/fil-soc.v32i3.4492
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Structural Methodology in Postmodern Concepts of Technology

Abstract: The article is aimed at defining the possibilities for structural methodology to understand the phenomenon of modern technology. Some principles of postmodernists’ structural research are highlighted. The embodiment of these principles in the analytical discourse is shown, considering the state and development of technical activities and how they allow one to assess and predict future events. These predictions about mechanization, informatization and virtualization of almost all areas of modern society are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The analysis of scientific publications on this theme showed that the problems of science methodology had become the subject of attention of domestic and foreign philosophers and scientists. The problems of the methodology of scientific research in the aspect of the relationship between philosophy and science are noted in the works of Chursinova (2021) Klimenyuk (2012), Leshhak (2002) and Nosirova (2023) are shedding light on the current state of linguistic methodology and its correspondence to the demands of the humanistic oriented culture of Postmodernism. The theme of the use of a narrative form in linguistics in the paradigm of the methodology of postmodernism is revealed in the works of Bekhta (2015), Mahkamova (2018), Marmolejo-Ramos et al (2014) and Onopriyenko (2010).…”
Section: Brief Review Of Philosophical and Scientific Literature On T...mentioning
confidence: 99%
“…The analysis of scientific publications on this theme showed that the problems of science methodology had become the subject of attention of domestic and foreign philosophers and scientists. The problems of the methodology of scientific research in the aspect of the relationship between philosophy and science are noted in the works of Chursinova (2021) Klimenyuk (2012), Leshhak (2002) and Nosirova (2023) are shedding light on the current state of linguistic methodology and its correspondence to the demands of the humanistic oriented culture of Postmodernism. The theme of the use of a narrative form in linguistics in the paradigm of the methodology of postmodernism is revealed in the works of Bekhta (2015), Mahkamova (2018), Marmolejo-Ramos et al (2014) and Onopriyenko (2010).…”
Section: Brief Review Of Philosophical and Scientific Literature On T...mentioning
confidence: 99%